The Tryptophan-Rich Sensory Protein (TSPO) is Involved in Stress-Related and Light-Dependent Processes in the Cyanobacterium Fremyella diplosiphon - Busch, Andrea W. U.; Montgomery, Beronda L. (Frontiers in Microbiology, 2015)
The tryptophan-rich sensory protein (TSPO) is a membrane protein, which is a member of the 18 kilodalton translocator protein/peripheral-type benzodiazepine receptor (MBR) family of proteins that is present in most organisms and is also referred to as Translocator protein 18 kDa. Although TSPO is associated with stress- and disease-related processes in organisms from bacteria to mammals, full elucidation of the functional role of the TSPO protein is lacking for most organisms in which it is found. In this study, we describe the regulation and function of a TSPO homolog in the cyanobacterium Fremyella diplosiphon, designated FdTSPO. Accumulation of the FdTSPO transcript is upregulated by green light and in response to nutrient deficiency and stress. A F. diplosiphon TSPO deletion mutant (i.e., ΔFdTSPO) showed altered responses compared to the wild type strain under stress conditions, including salt treatment, osmotic stress and induced oxidative stress. Under salt stress, the FdTSPO transcript is upregulated and a ΔFdTSPO mutant accumulates lower levels of reactive oxygen species (ROS) and displays increased growth compared to WT. In response to osmotic stress, FdTSPO transcript levels are upregulated and ΔFdTSPO mutant cells exhibit impaired growth compared to the wild type. By comparison, methyl viologen-induced oxidative stress results in higher ROS levels in the ΔFdTSPO mutant compared to the wild type strain. Taken together, our results provide support for the involvement of membrane-localized FdTSPO in mediating cellular responses to stress in F. diplosiphon and represent detailed functional analysis of a cyanobacterial TSPO. This study advances our understanding of the functional roles of TSPO homologs in vivo.